2017
DOI: 10.1186/s12889-016-3934-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a school-based intervention on active commuting to school and health-related fitness

Abstract: BackgroundActive commuting to school has declined over time, and interventions are needed to reverse this trend. The main objective was to investigate the effects of a school-based intervention on active commuting to school and health-related fitness in school-age children of Southern Spain.MethodsA total of 494 children aged 8 to 11 years were invited to participate in the study. The schools were non-randomly allocated (i.e., school level allocation) into the experimental group (EG) or the control group (CG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
0
38
0
3
Order By: Relevance
“…34 Contrary to our findings in both sexes, the Danish study did not find an association between AST and speed and agility assessed by the 4 × 10 m shuttle run test, although the age of their sample differed from ours in the present study (ie, children vs adolescents). 33 A quasi-experimental study that focused on increasing children's AST did not report increases in health-related fitness in boys or girls, 36 suggesting that more research with a randomized clinical trial design is needed.…”
Section: Discussionmentioning
confidence: 99%
“…34 Contrary to our findings in both sexes, the Danish study did not find an association between AST and speed and agility assessed by the 4 × 10 m shuttle run test, although the age of their sample differed from ours in the present study (ie, children vs adolescents). 33 A quasi-experimental study that focused on increasing children's AST did not report increases in health-related fitness in boys or girls, 36 suggesting that more research with a randomized clinical trial design is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The only prospective investigation screened showed that active commuting by cycling in children over a span of six years, increased the PF in 14% [33]. On the other hand, in four studies an association between active commuting and PF was not observed [3,29,32,34]. In one study, mixed results were observed.…”
Section: Children/adolescentmentioning
confidence: 93%
“…From the 11 studies focused on children/adolescents, four were performed in Spain, two in England, two in Norway, one in Sweden, one in Brazil, and one in Colombia. Furthermore, eight were cross-sectional [3,12,[27][28][29][30][31][32], one prospective cohort [33], one quasi-experimental [34], and one experimental [35]. The CRF was the PF attribute assessed the most (nine studies), while MF was assessed in three studies [3,27], and agility in two studies [3,31].…”
Section: Children/adolescentmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion was based on several reasons. First, although preceding studies discovered a 73% agreement between PALMS bicycling and SenseCamp trips [18], the percentages of youth cycling to school in Spain were low (≈1%) [27,28]. Secondly, in the Portuguese study, the cycling trips were overestimated based on the same method to categorize trips, i.e., GPS and PALMS software [10].…”
Section: Discussionmentioning
confidence: 83%